INTERNET OF THINGS UNTUK MONITORING KONDISI AIR BUDIDAYA IKAN KELOMPOK ‘TUTUT JAYA’ KOTA MALANG - Fitriana, Nurin; Darmawan, Azhar Adi; Rahmawati, Mariana Fitri (LPPM Universitas Nusa Mandiri, 2024)
This service aims to improve the skills and knowledge of catfish farmers in the